2021
DOI: 10.5812/aapm.112424
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Risk Score for Mechanical Ventilation in Hospitalized Adult Patients Suffering from COVID-19

Abstract: Background: COVID-19 has become a pandemic since December 2019, causing millions of deaths worldwide. It has a wide spectrum of severity, ranging from mild infection to severe illness requiring mechanical ventilation. In the middle of a pandemic, when medical resources (including mechanical ventilators) are scarce, there should be a scoring system to provide the clinicians with the information needed for clinical decision-making and resource allocation. Objectives: This study aimed to develop a scoring system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Several factors are associated with intubation in COVID-19 patients. Elderly patients, male patients, and those with background diseases, particularly hypertension and diabetes, are more at risk of intubation (1,15,35,56). Also, chest CT scan and respiratory rate are important prognostic factors in determining the severity of the disease and overall prognosis (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors are associated with intubation in COVID-19 patients. Elderly patients, male patients, and those with background diseases, particularly hypertension and diabetes, are more at risk of intubation (1,15,35,56). Also, chest CT scan and respiratory rate are important prognostic factors in determining the severity of the disease and overall prognosis (59).…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, more than 10% of COVID-19 patients in northern Italy who suffered from hypoxia were intubated in the ICU (14). It is reported that old age, diabetes mellitus, respiratory rate, increased level of C-reactive protein, bicarbonate level, and oxygen saturation are the most valuable predictors of the need for mechanical ventilation (15). One of the distinguishing characteristics of hypoxia in COVID-19 patients is "the happy hypoxic", which means that the patient is mentally alert and there is no significant respiratory distress, but low blood oxygen saturation can be developed (16).…”
Section: Introductionmentioning
confidence: 99%
“…been conducted globally to discover a feasible, effective treatment. Unfortunately, critically ill and mechanically ventilated patients suffering COVID-19 show an overall higher mortality rate (10)(11)(12). Although vaccine development offers a glimmer of hope to end the current appalling pandemic, there is still a lack of definitive therapy, particularly for SARS-CoV-2-induced pneumonia (13).…”
Section: Contextmentioning
confidence: 99%
“…The lung mechanic indices are well-preserved in the first days of the disease, and there is no increased airway resistance or dead space ventilation; thus, the respiratory center does not sense an uncomfortable sensation of breathing. Considering ARDS as the most common reason for mortality in COVID-19 patients and concurrent happy/silent hypoxemia on the first day of the disease, it seems that prediction scores that rely on pulmonary variables (such as partial pressure of oxygen [Pao 2 ], Pao 2 /fraction of inspired oxygen [Fio 2 ]) can be misleading in diagnosing the severe/critically ill COVID-19 patients (12)(13)(14)(15).…”
mentioning
confidence: 99%